Pengaruh Brand Trust, Celebrity Endorse dan Brand Image Terhadap Keputusan Pembelian Produk Vaseline di Kota Batam - Waruwu, Hernita Sari; Suhardi, Suhardi (SCIENTIA JOURNAL, 2025)
Consumer purchasing decisions are actions taken by consumers before making a purchase of a desired product. This study aims to determine the influence of brand trust, celebrity endorsement , and brand image on purchasing decisions for Vaseline products in Batam City. This study uses quantitative techniques. The population used is users who have used Vaseline products. The sampling technique uses the Lemeshow formula with a calculation of 100 respondents with a purposive sampling technique . Data were analyzed using a multiple linear regression model with data quality testing, classical assumption testing, influence testing, and hypothesis testing. The results of the multiple linear regression analysis indicate that brand trust and celebrity endorsement variables have no significant effect on purchasing decisions. In contrast, the brand image variable shows a positive and significant effect on purchasing decisions. Simultaneously, the three independent variables influence purchasing decisions with a contribution of 62.1%. This finding underscores the importance of strengthening brand image as a key factor in marketing strategies, while the effectiveness of celebrity endorsement and brand trust on purchasing decisions needs to be reviewed by the company. Keywords: Brand Trust, Celebrity Endorsement, Brand Image, Purchasing Decis